2014
DOI: 10.1038/nphys2980
|View full text |Cite
|
Sign up to set email alerts
|

Pancake bouncing on superhydrophobic surfaces

Abstract: Engineering surfaces that promote rapid drop detachment1,2 is of importance to a wide range of applications including anti-icing3–5, dropwise condensation6, and self-cleaning7–9. Here we show how superhydrophobic surfaces patterned with lattices of submillimetre-scale posts decorated with nano-textures can generate a counter-intuitive bouncing regime: drops spread on impact and then leave the surface in a flattened, pancake shape without retracting. This allows for a four-fold reduction in contact time compare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
737
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 839 publications
(761 citation statements)
references
References 30 publications
21
737
3
Order By: Relevance
“…Regular arrays of vertical pillars are commonly used in experiments in order to generate superhydrophobic surfaces [1,24,27,42]. For the experiments of Maitra et al [26] in which entrapped gas bubbles are observed in the substrate, the height of the pillars forming the substrateh is of the order of 10 µm.…”
Section: Gas Behaviour In the Substratementioning
confidence: 99%
“…Regular arrays of vertical pillars are commonly used in experiments in order to generate superhydrophobic surfaces [1,24,27,42]. For the experiments of Maitra et al [26] in which entrapped gas bubbles are observed in the substrate, the height of the pillars forming the substrateh is of the order of 10 µm.…”
Section: Gas Behaviour In the Substratementioning
confidence: 99%
“…A rich body of literature already exists considering perpendicular drop impacts, with a droplet falling from above onto a flat surface [1][2][3][4][5][6][7][8]. These studies have revealed the underlying mechanics and possible outcomes of droplet splashing and are industrially relevant to processes such as spray coating, spray cooling and inkjet printing.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet impacts on superhydrophobic (SHP) surfaces have gained recent attention because the non-wetting nature of such surfaces provokes entirely new impact behaviours such as rebounding, partial rebounding, and pancake bouncing [2,3]. Superhydrophobicity is a surface's ability to easily repel water droplets and resist wetting.…”
Section: Introductionmentioning
confidence: 99%
“…Whether an impacting droplet 1 sticks or not to a solid surface has been conventionally controlled by functionalizing the target surface [2][3][4][5][6][7][8] or by using additives in the drop 9,10 . Here we report on an unexpected self-peeling phenomenon that can happen even on smooth untreated surfaces by taking advantage of the solidification of the impacting drop and the thermal properties of the substrate.…”
mentioning
confidence: 99%